Estimation of counting efficiencies of a portable NaI detector using Monte Carlo simulation for thyroid measurement following nuclear accidents. (6th July 2017) - Ha, Wi-Ho; Kim, Jong Kyung; Jin, Young Woo
Abstract: Radioiodine can be released in nuclear accidents and can cause internal contamination of the thyroid gland in members of the public. For population monitoring in radiation emergencies, measurement of counting efficiency is very important to accurately determine thyroid activity. Here, we estimate the counting efficiencies of a portable NaI detector using Monte Carlo simulations. Two different types of neck phantoms and a 7.62 cm long by 7.62 cm diameter NaI detector were modeled and the counting efficiencies were calculated depending on the thyroid size and distance from the neck phantom to the detector. We found that distance is a more important parameter than thyroid size. The optimal distance of the NaI detector from the neck surface was determined to be greater than 12 cm, beyond which the counting efficiency was not affected by thyroid size.